STRATEGI EDUKASI TENTANG PENANGANAN AWAL INTOKSIKASI MAKANAN DALAM TANGGAP KEGAWATDARURATAN - Diana Rachmania; Dhina Widayati (STIKES dan AKZI Karya Husada Kediri, 2022)
One of the emergency events that threaten human life in the digestive system is food poisoning. Food poisoning is a serious health problem that can lead to severe illness and even death. The purpose of this service activity was to find out the benefits of an Educational Strategy on Early Handling of Food Intoxication (Poisoning) in Emergency Response. The activity method used in this activity is the lecture and discussion method where the service team provides education about the initial handling of food intoxication in emergency response. Participants in this activity were students of PMR SMAN 1 Gurah totaling 20 participants. The media used in educational activities are leaflets. The measuring tool for assessing knowledge before and after the activity is in the form of a questionnaire. The result of this activity is that there is an increase in students' knowledge about the initial treatment of food intoxication where the average value of the pres test is 60/100 and after being given health education, the post test score increases with an average value of 80/100. The activity in the form of an educational strategy on the initial handling of food intoxication is expected to increase the knowledge of PMR members so that it can be applied if there are victims of food intoxication